Invertebrates of Siberia as a promising source of animal protein for innovative feed and food production. 6. Potential of nutrient accumulation in biomass via feed enrichment - Sergei E. Tshernyshev; Andrei S. Babenko; Irina B. Babkina; Ruslan T-O. Baghirov; Vera P. Modyaeva; Margarita D. Morozova; Ksenia E. Skriptcova; Elena Yu. Subbotina; Mikhail V. Shcherbakov; Anastasia V. Simakova (Acta Biologica Sibirica)
This study investigates the feasibility of designing the nutrient composition of four model species of terrestrial invertebrates, namely: two insects, the House cricket (Acheta domesticus (Linnaeus, 1758)) and the Speckled cockroach (Nauphoeta cinerea (Olivier, 1789)), the Giant African land snail (Lissachatina fulica (Férussac, 1821)), and the oligochaete compost worm (Eisenia fetida (Savigny, 1826)), through the modification of the feeding substrate composition to obtain biomass with specified parameters of nutrients. It was established that the addition of B-vitamins to the feeding substrate leads to an increase in their content in invertebrates, with the greatest effect observed in insects. In some cases, doubling the dose of these vitamins in the feeding substrate yields a positive effect and promotes greater vitamin accumulation in the animal organisms. The study demonstrated that the addition of fat-soluble vitamins to the feeding substrate also contributes to an increase in their levels in the investigated species. Doubling the dose has a positive effect on crickets, snails, and worms, while a single dose is sufficient for cockroaches. No significant changes in the content of micro- and macroelements were observed in any of the four invertebrate species when mineral substances were added to the diet. In terms of protein content, all studied invertebrates were comparable, while insects had significantly higher levels of fats, carbohydrates, and chitin. The addition of nutrients (substrate with a double dose of vitamins B7 and C, a mineral complex additive, fat-soluble vitamins, and B-complex vitamins) increased the content of fats, proteins, and carbohydrates in insects, as well as ash content in snails and worms. Insects are twice as caloric as snails and worms, and the caloric content of insects increases with the addition of nutrients, while that of snails and worms remains unchanged. Our experiments have shown that it is possible to control the content of vitamins, fats, proteins, and carbohydrates in the biomass of invertebrates, as well as the caloric content in insects by enriching the feeding substrate with precursors. In contrast, the addition of mineral substances to the feeding substrate does not lead to changes in the content of micro- and macroelements in the studied species. Insects are more susceptible to changes in nutrient composition, being enriched with a greater variety of vitamins, proteins, fats, and carbohydrates, and they are significantly more caloric. Therefore, they are the most promising candidates for biomass production with specified properties.